Treatment of poor-risk myelodysplastic syndromes and acute myeloid leukemia with a combination of 5-azacytidine and valproic acid - Kuendgen, Andrea (Springer-Verlag, 2011)
5-azacytidine (AZA) has become standard treatment for patients with higher-risk myelodysplastic syndrome (MDS). Response rate is about 50% and response duration is limited. Histone deactylase (HDAC) inhibitors are attractive partners for epigenetic combination therapy. We treated 24 patients with AZA (100 mg/m(2), 5 days) plus valproate (VPA; continuous dosing, trough serum level 80–110 μg/ml). According to WHO classification, 5 patients had MDS, 2 had MDS/MPD, and 17 had acute myeloid leukemia (AML). Seven patients (29%) had previously received intensive chemotherapy, and five had previous HDAC inhibitor treatment. The overall response rate was 37% in the entire cohort but significantly higher (57%) in previously untreated patients, especially those with MDS (64%). Seven (29%) patients achieved CR (29%) and two PR (8%), respectively. Hematological CR was accompanied by complete cytogenetic remission according to conventional cytogenetics in all evaluable cases. Some patients also showed complete remission according to FISH on bone marrow mononuclear cells and CD34(+) peripheral blood cells, as well as by follow-up of somatic mitochondrial DNA mutations. Four additional patients achieved at least marrow remissions. Factors influencing response were AML (vs. MDS), marrow blast count, pretreatment, transfusion dependency, concomitant medication with hydroxyurea, and valproic acid (VPA) serum level. This trial is the first to assess the combination of AZA plus VPA without additional ATRA. A comparatively good CR rate, relatively short time to response, and the influence of VPA serum levels on response suggest that VPA provided substantial additional benefit. However, the importance of HDAC inhibitors in epigenetic combination therapy can only be proven by randomized trials.